Scientific Validation of Gentiana kurroo Royle for Anti-Inflammatory and Immunomodulatory Potential. (23rd February 2014) - Mubashir, Khan; Ghazanfar, Khalid; Ganai, Bashir A.; Akbar, Seema; Malik, Akhtar H.; Masood, Akbar
Abstract : Gentiana kurroo Royle is a critically endangered medicinal plant species endemic to the northwestern Himalayas. This plant was studied for the immunomodulatory and anti-inflammatory potential. Carrageenan paw edema model was used to study the potential of the drug in inflammation in Wistar rats. SRBC specific haemagglutination titre and DTH assays were carried out in Balb/C mice for observing the effect of test drugs on immune system. The plant extracts were found to be active against inflammation. The methanolic fraction was observed to be the most effective in inhibition of paw edema with the inhibitory potential of 47.62%. In immunomodulation studies the plant extracts showed the immunosuppressant activity. Methanolic fraction was observed to have maximum potential for the suppression of both humoral (57.57% and 54.05%) and cell mediated immunity (65.27% and 75%). From these studies, it can be concluded that the extracts of plant are having anti-inflammatory and immunosuppressant activity. Since in chronic inflammation like arthritis there is the involvement of immune system, this plant may serve as an alternative for the treatment of autoimmune diseases like arthritis.